Pengaruh Lingkungan Kerja dan Motivasi Terhadap Kinerja Karyawan Bagian Produksi di PT Bokor Mas Mojokerto - Muhammad Afif Rosyikhuddin (BIMA : Journal of Business and Innovation Management, 2018)
PT. Bokormas Mojokerto is a manufacturing company that produces kretek cigarettes and filters for the domestic cigarette market in Indonesia. PT. Mojokerto Bokormas is a class II cigarette company with a medium scale. Cigarettes produced by PT. Bokormas namely SKM (Machine Clove Cigarettes), SKT (Hand Kretek Cigarettes), and Klobot. Bokormas is interpreted as a large golden bowl in ancient Javanese-Indonesian language. In this study aims to find out: 1) the influence of the work environment on the performance of the production part employees at PT Bokor Mas Mojokerto, 2) the influence of motivation on the performance of production employees at PT Bokor Mas Mojokerto, 3) the influence of the work environment and motivation together on the performance of employees in the production section at PT Bokor Mas Mojokerto. This study uses 2 types of data, namely primary and secondary data, the research method involves 2 variables: independent variable (employee performance), and dependent variable (work environment and motivation). This type of research uses a type of causal research which is a form of causal relationship with a quantitative approach. Sampling was determined by simple random sampling technique taken as many as 75 employees. Based on the results of calculations using SPSS version 23 shows that: 1) the work environment variable partially has a significant effect on employee performance, with t count of 2.321> t table 1.66 with a significant value of 0.023. 2) motivation variable partially there is a significant effect on employee performance with a tcount of 4.060> ttable1.66 with a significant value of 0.000. 3) the work environment and motivation variables simultaneously have an effect on employee performance, with a Fcount of 14.684 <Ftable3.12 and a significant level of 0.000.